Spectrum of Pediatric to Early Adulthood POLR3A‐Associated Movement Disorders. Issue 2 (23rd December 2022) - Zea Vera, Alonso; Bruce, Adrienne; Larsh, Travis R.; Jordan, Zachary; Brüggemann, Norbert; Westenberger, Ana; Espay, Alberto J.; Gilbert, Donald L.; Wu, Steve W.
ABSTRACT: Background: POLR3A pathogenic variants are associated with hypomyelination, hypodontia, hypogonadism, and movement disorders. Cases: We describe the range of movement disorders seen in six patients (four female, two male) with POLR3A variants [three novel (c.2214del, c.3775G>A, c.3905G>T) and six previously reported (c.760C>T, c.1771‐7C>G, c.1909+22G>A, c.2005C>T, c.2422C>T, c.3337‐11T>C)]. Patient 1 presented with a neonatal progeroid syndrome and developed parkinsonism, dystonia, ataxia, and spasticity. Patient 2 presented with infant‐onset rapidly progressive chorea, and dystonia. Three patients (patients 3, 5, 6) presented predominantly with ataxia in combination with spasticity and dystonia. Patient 4 developed segmental dystonia during adolescence and ataxia in early adulthood. Four patients had vertical gaze impairment. The most common brain MRI abnormality was T2‐weighted/FLAIR hyperintensity of the superior cerebellar peduncles and midbrain. Conclusion: POLR3A ‐related disorders exhibit significant phenotypic pleomorphism. Vertical gaze dysfunction and T2‐weighted/FLAIR hyperintensity of the superior cerebellar peduncles and midbrain may be useful signs suggestive of this condition.